Eonomic and social panorama of the Community of Latin America and Caribbean states 2014- - Oviedo, Enrique (ECLAC, 2015)
Summarises the situation in Latin America and the Caribbean in relation to economic, social and population affairs, as well as foreign direct investment, trade and gender equality.